Marketing Strategy Analysis: The Effect of 7P Marketing Mix on School Choice Decision Using PLS-SEM in Bekasi - Aprilliantoni Aprilliantoni (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the influence of the 7P marketing mix on parents’ school choice decisions in the increasingly competitive private education sector in Bekasi, Indonesia. It addresses the limited evidence on the simultaneous effects of all seven marketing mix dimensions on school selection. Design/Methodology/Approach – A quantitative cross-sectional design was employed. Data were collected from 202 parents and prospective parents using purposive sampling and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The results indicate that promotion, process, and physical evidence significantly influence school choice decisions, with process emerging as the strongest predictor. In contrast, product, price, place, and people have no significant effect. Originality/Value – This study extends educational marketing research by simultaneously examining the complete 7P marketing mix framework in private school selection. The findings provide practical guidance for private schools to strengthen enrollment by prioritizing promotional strategies, improving service processes, and enhancing physical facilities.